Gastrobronchial Fistula after Robotic Repair of Traumatic Diaphragmatic Hernia - Jamie T. Tung; Leah M. Lucero; James W. Davis; Lawrence P. Sue (Case Reports in Surgery)
Gastrobronchial fistulas are a rare occurrence in the literature. We report a case of a gastrobronchial fistula after robotic repair of a chronic traumatic diaphragmatic hernia. The patient had severe respiratory symptoms with multiple studies that were inconclusive. The fistula was ultimately discovered after an esophagogastroduodenoscopy (EGD). The patient underwent a left thoracotomy for takedown of his fistula and eventually recovered. Earlier EGD and a lower threshold for differential that included this diagnosis would have led to an earlier identification and treatment of a rare disease process.